Contribution of Altered Endocannabinoid System to Overactive mTORC1 Signaling in Focal Cortical Dysplasia - García-Rincón, Daniel; Díaz-Alonso, Javier; Paraíso-Luna, Juan; Ortega, Zaira; Aguareles, José; de Salas-Quiroga, Adán; Jou, Cristina; de Prada, Inmaculada; Martínez-Cerdeño, Verónica; Aronica, Eleonora; Guzmán, Manuel; Pérez-Jiménez, María Ángeles; et al. (Frontiers in Pharmacology, 2019)
Alterations of the PI3K/Akt/mammalian target of rapamycin complex 1 (mTORC1) signalling pathway are causally involved in a subset of malformations of cortical development (MCDs) ranging from focal cortical dysplasia (FCD) to hemimegalencephaly and megalencephaly. These MCDs represent a frequent cause of refractory paediatric epilepsy. The endocannabinoid system -especially cannabinoid CB1 receptor- exerts a neurodevelopmental regulatory role at least in part via activation of mTORC1 signalling. Therefore, we sought to characterize the possible contribution of endocannabinoid system signalling to FCD. Confocal microscopy characterization of the CB1 receptor expression and mTORC1 activation was conducted in FCD Type II resection samples. FCD samples were subjected to single nucleotide polymorphism screening for endocannabinoid system elements, as well as CB1 receptor gene sequencing. Cannabinoid CB1 receptor levels were increased in FCD with overactive mTORC1 signalling. CB1 receptors were enriched in phospho-S6-positive cells including balloon cells (BC) that co-express aberrant markers of undifferentiated cells and dysplastic neurons. Pharmacological regulation of CB1 receptors and the mTORC1 pathway was performed in fresh FCD-derived organotypic cultures. HU-210-evoked activation of CB1 receptors was unable to further activate mTORC1 signalling, whereas CB1 receptor blockade with rimonabant attenuated mTORC1 overactivation. Alterations of the endocannabinoid system may thus contribute to FCD pathological features, and blockade of cannabinoid signalling might be a new therapeutic intervention in FCD.